-x(7x-8)=

Simple and best practice solution for -x(7x-8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x(7x-8)= equation:


Simplifying
-1x(7x + -8) = 0

Reorder the terms:
-1x(-8 + 7x) = 0
(-8 * -1x + 7x * -1x) = 0
(8x + -7x2) = 0

Solving
8x + -7x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(8 + -7x) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(8 + -7x)' equal to zero and attempt to solve: Simplifying 8 + -7x = 0 Solving 8 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -7x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -7x = 0 + -8 -7x = 0 + -8 Combine like terms: 0 + -8 = -8 -7x = -8 Divide each side by '-7'. x = 1.142857143 Simplifying x = 1.142857143

Solution

x = {0, 1.142857143}

See similar equations:

| 4(t-2)+4t=4(2t+5)-10 | | 12x^2-23x+10=0 | | 33+4x=-(x+7) | | 4(x-6)=12-(x+3) | | 2a^9-32a= | | (9x+1)(5x-2)=0 | | -24r=72 | | log[4](2x+3)=0 | | 8x-8+7x+8+6x+12=180 | | 8+2y-1=9y+14-6y | | 2x+13-4x=18-19x+17x-5 | | 4c-3=2c+7 | | x=180-6y | | 119-(7x+3)=7(x+8)+x | | 7x-3=7x-3 | | 4x^2+18x+20=90 | | -4+s^2= | | 3(x+1)=34(x+23) | | 3(1-2x)+12=10-2(x-39) | | 3/8-3/4=x | | 9s^2-24s+16= | | 24x-4-8x+26=15x+25 | | 5t-8=-28+t | | x^2-4x+1=5 | | 8.2x-2.3x=-94.4 | | 6x^3+10x^2+21x-35=0 | | (4a^3-4a^2)+(6a^3+5a^2)=0 | | 9s^2+24s+16= | | 3x-(-2x+2)=6-(2x-4) | | 3y-(2y-4)=5y | | 12+0.35=20.05 | | 25a^4b^7c^9-75a^8b^9c^10= |

Equations solver categories